Bronze Age monuments and Bronze Age, Iron Age, Roman and Anglo-Saxon landscapes at Cambridge Road, Bedford - Chapman, Andy 1951-; Chapman, Pat (Archaeopress Publishing Ltd, 2017)
Open area excavation on 14.45ha of land at Cambridge Road, Bedford was carried out in 2004-5 in advance of development. A background scatter of Early Neolithic flint, including a Langdale stone axe, may be related to the nearby presence of the Cardington causewayed enclosure
Previously issued in print: 2017. - Includes bibliographical references
Keywords: Vor- und Frühgeschichte; Excavations (Archaeology) / England / Bedford; Funde; Ausgrabung; Bedford (England) / Antiquities; Bedford